Mitotically Active Follicular Nodule in Early Childhood: A Case Report with a Novel Mutation in the Thyroglobulin Gene - Sirmen Kızılcan Çetin; Zehra Aycan; Zeynep Şıklar; Serpil Dizbay Sak; Serdar Ceylaner; Elif Özsu; Merih Berberoğlu (Galenos Yayincilik, 2024)
Dyshormonogenesis (DG) is the failure of thyroid hormone production due to a defect in thyroid hormonogenesis. Loss-of-function mutations in the thyroglobulin (TG) gene are a cause of DG, leading to gland stimulation by thyroid-stimulating hormone (TSH), resulting in goiter. We report a mitotically active follicular nodule in an 11-year-old female with a novel mutation in the TG gene. The patient had been under follow-up for congenital hypothyroidism (CH) since the neonatal period, and she had normal TSH levels on replacement therapy. Genetic test revealed a novel compound heterogeneous mutation [c.2149C>T (p.R717*) (P.Arg717Ter) / c.5361_5362delCCinsG (p.H1787Qfs*3) (p.His1787GlnfsTer3)] in the TG gene. She underwent total thyroidectomy for a thyroid nodule that was reported as Bethesda IV on fine needle aspiration biopsy (FNAB) and noted as suspicious for noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP). Pathological examination revealed a 16 mm, well-demarcated follicular nodule with a solid/insular pattern. Mitotic activity and Ki67 proliferation index were unusually high (10 mitoses/mm2 and 10%, respectively). Marked cellular pleomorphism and nuclear atypia are well-known diagnostic pitfalls in patients with dyshormonogenetic goiter. However, high mitotic activity is a feature that is less commonly reported in dyshormonogenetic goiter and may raise suspicion of poorly differentiated carcinoma when observed together with a solid pattern. The absence of signs of invasion, history of CH, and awareness of the presence of mutations compatible with dyshormonogenetic goiter can prevent the overinterpretation of such lesions. The risk of cancer development in the dyshormonogenetic thyroid gland is possible in childhood. The close follow-up is life-saving and prevents morbidities and possible mortality.